Using virtual reality in museums to bridge the gap between material heritage and the interpretation of its immaterial context - Cunha, Carlos R. (2022)
Material heritage typically has a whole set of associated immaterial heritage, which is essential to pass on to the visitor as a cultural mission of the destinations and those who manage them. In this sense, the interpretation of material heritage is a complex process that is not a fully efficient process with the mere observation of physical artifacts. In this context, it emerges as fundamental to provide visitors with a set of tools that allow them to correctly interpret the artifacts that come to fully understand the cultural dimension of the destinations and their heritage. Accordingly, the role of virtual reality can leverage the creation of innovative and immersive solutions that allow the visitor to understand and feel part of their own heritage and its ancestral component that defines the sociocultural roots of destinations and their civilizational traditions. This article, after dissecting and substantiating the role of virtual reality in the interpretation of heritage, presents a conceptual model, based on the use of virtual reality, which was, in part, prototyped in the scenario of the Portuguese Museum in the city of Miranda do Douro. This proposal is an ongoing contribution to the creation of innovative and immersive tools for the interpretation of heritage.